The Comprehensive and Progressive Agreement for Trans-Pacific Partnership. - Lee.; Bhattacharya (Singapore : ISEAS - Yusof Ishak Institute, 2021)
"The Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) is a free trade agreement involving major countries across the Asia Pacific region. The trade pact, which entered into force on 30 December 2018, is considered by many to be the "gold standard", given its ambitious scope and depth. This volume offers multi-dimensional insights into the CPTPP and its impact on Southeast Asia. It begins with broad analyses covering the historical, economic and geopolitical aspects of the CPTPP. Subsequent chapters focus on the nature and implications of three key path-breaking provisions in the trade agreement, namely investor-state dispute settlement, intellectual property rights and state-owned enterprises. The effect of the CPTPP on Southeast Asia in terms of regional production networks is also examined from the perspective of Japanese multinational enterprises. The potential economic impact of the agreement is analysed for member countries (Vietnam and Malaysia) as well as countries that aspire to join the CPTPP in the future (Indonesia and Thailand). The world trading system is in disarray: the World Trade Organization has been weakened, perhaps terminally; the world's two economic superpowers are locked in deep, politicized disputes; the forces of populism and nationalism are everywhere complicating the return to a more liberal, rules-based order. These trends are challenging one of the building blocks of ASEAN economic development, namely these countries' outward-looking trade and investment policies. With impeccable timing this important volume by a group of eminent authors assesses these issues with reference to the Comprehensive and Progressive Agreement for Trans-Pacific Partnership. The CPTPP excludes the three largest traders--China, the EU and the US--but it is a welcome second-best initiative that may have broader
positive ripple effects. This is the volume to read to gain a deeper understanding of the many complex issues at play." -- Hal Hill, H.W. Arndt Professor Emeritus of Southeast Asian Economies, College of Asia & the Pacific, Australian National University.
Intro -- Contents -- 1. Introduction -- 2. The Economics of the CPTPP and RCEP: Asia Pacific Trade Agreements without the United States -- 3. The TPP and CPTPP: Truths about Power Politics -- 4. The Investment Chapter and ISDS in the CPTPP: Lessons from and for Southeast Asia -- 5. Intellectual Property in the CPTPP and Access to Medicines: A Thai Perspective -- 6. New Rules for State-Owned Enterprises in the CPTPP -- 7. Impact of the CPTPP on Japanese Manufacturing Affiliates in ASEAN -- 8. Reassessing Malaysia's Export Opportunities in the TPP and CPTPP -- 9. Impact of the CPTPP on Vietnam -- 10. Should Thailand Join the CPTPP? -- 11. Indonesia, the TPP and CPTPP: Hold Your Breath -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books